TEACHING SCIENCE USING ENGLISH DONE BY PRIMARY SCHOOL TEACHERS IN MALANG - Pritha Anggiarima (University of Muhammadiyah Malang, 2019)
English as a Medium of Instruction (EMI) is relied by many teachers to achieve bilingual education goals. The purpose of teaching any other subjects in English is to prepare the students to learn from the firsthand sourcewhen later they pursue higher education. However, there are some challenges when it comes to the practice in young learners. This paper discusses the strategies and problems faced by science teachers in bilingual primary schools in Malang. A questionnaire was distributed to all science teachers who were delivering their lesson in English to determine their educational background, strategies, experiences, and obstacles when they were teaching Science using English. The researcher also asked them about the textbook they used and the students’ average score in Science. As a result, it can be analyzed how successful the teaching of Science using English in bilingual primary schools in Malang.